Modulation of The Electron Beams Depths Dose Distribution Via 3D Printed Plastic Samples; Electron, Positron, Neutron and X–ray Scattering under External Influences - Bushmina E. A. Elizaveta Alekseevna; Bulavskaya A. A. Angelina Aleksandrovna; Cherepennikov Yu. M. Yuriy Mihaylovich; Grigorieva (Grigorjeva) A. A. Anna Anatoljevna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich (2021, 2021)
Title screen